Glycated hemoglobin correlates with arterial stiffness and endothelial dysfunction in patients with resistant hypertension and uncontrolled diabetes mellitus. Issue 5 (5th May 2018) - Moreno, Beatriz; de Faria, Ana Paula; Ritter, Alessandra Mileni Versuti; Yugar, Lara Buonalumi Tacito; Ferreira‐Melo, Silvia Elaine; Amorim, Rivadavio; Modolo, Rodrigo; Fattori, André; Yugar‐Toledo, Juan Carlos; Coca, Antonio; Moreno, Heitor
Abstract : This study aimed to evaluate the effects of glycated hemoglobin (HbA1c ) on flow‐mediated dilation, intima‐media thickness, pulse wave velocity, and left ventricular mass index in patients with resistant hypertension (RHTN) comparing RHTN–controlled diabetes mellitus and RHTN–uncontrolled type 2 diabetes mellitus. Two groups were formed: HbA1c <7.0% (RHTN–controlled diabetes mellitus: n = 98) and HbA1c ≥7.0% (RHTN–uncontrolled diabetes mellitus: n = 122). Intima‐media thickness and flow‐mediated dilation were measured by high‐resolution ultrasound, left ventricular mass index by echocardiography, and arterial stiffness by carotid‐femoral pulse wave velocity. No differences in blood pressure levels were found between the groups but body mass index was higher in patients with RHTN–uncontrolled diabetes mellitus. Endothelial dysfunction and arterial stiffness were worse in patients with RHTN–uncontrolled diabetes mellitus. Intima‐media thickness and left ventricular mass index measurements were similar between the groups. After adjustments, multiple linear regression analyses showed that HbA1c was an independent predictor of flow‐mediated dilation and pulse wave velocity in all patients with RHTN. In conclusion, HbA1c may predict the grade of arterial stiffness and endothelial dysfunction in patients with RHTN, and superimposed uncontrolled diabetes mellitus implicates further impairment of vascular function.